KEMAMPUAN Ca(OHh MENURUNKAN KADARS02 PADA EMISI GAS BUANG MOTOR DIESEL - Merlita Novia Veronica; S B Ekowarno; Rachmaniyah . (Poltekkes Kemenkes Surabaya, 2014)
Sulfur dioxide is a major constituent of exhaust gas generated by diesel engines. The mainimpact of SOx (S02 and S03) contaminant is the generation of very sharp odor, the eventualoccurrence of corrosive acid rain, where as to humans such contaminants may cause irritation to eyes,skin and repiratory systems, and may prove to b fatal.The final produeNtf chemical reaction, H2S04 may cause corrosiveness, acid rain, and irritationto the eyes, skin, and respiratory tract, and may even be fatal, therefore it is deemed necessary toinitiate control of exhaust emissions from diesel engines. One of the many methods is the use of asaturated solution of lime water (CaOH2)as absorbent to reduce the said emissions.The purpose of this study was to determine the capacity of a saturated aqueous solution of limeor Ca (OH) 2 in lowering the levels of S02 in the flue gas emission from diesel engines (mobilesources).This is a pre-experimental study using One Group Pre-PostTest Design, this study was carriedout by conducting measurements on 6 samples of diesel engine exhaust emissions where 2 (two)measurements were done before and 4 (four) samples after passing through saturated lime waterabsorbent (CaOH2). Duration of sampling ranged between 20 -25 minutes.The results indicated the average levels of SOx before passing through saturated lime water(CaOH2) was 117,355 mg/m3 and the mean level of S02 after passing through a saturated lime waterwas 79,90 mg/m3. There was a decline in the average levels of S02 at a value of 37,455 mgr/m3 orby 31,90%This study concluded, that the lime water (CaOH2)solution was able to reduce the level of S02in exhaust emissions of a diesel engines by 37,455 mgr/m3 or 31,90%.It is suggested to owners of diesel engine motor vehicles to always perform proper maintenanceof their vehicles, and citizens (especially those living on the outskirt of a highway), in order to helppreserving the environment, are expected to plant trees and various other plants that can absorbcontaminants or can be used as indicators of pollution by motor vehicle exhaust emissions. The studyalso recommended to study other kinds of pollutant gase